Relasi Negara dan Agama dalam Pemikiran Politik Islam di Indonesia (Analisis Pemikiran Politik Nurcholish Madjid dan M. Natsir) - Imamah Syarifah; Ahmad Fauzan (Manabia: Journal of Constitutional Law, 2022)
State and religion relations are interesting things to discuss or become a subject of discussion that is still being debated from ancient times to the present. Always experiencing differences between the views of one character with another character. Because there is no standard concept of how to place the state and religion, in this case Islam in the State of Indonesia. For example, in the Indonesian context, when the constituents are trying to compile the latest Constitution, they are faced with two problems, namely Pancasila or Islam. Where there are interests between secular nationalist groups and Islamic nationalists. After a political agreement between the two groups, the 1945 Constitution was finally re-established in a Presidential Decree. Meanwhile, the issue of state and religion relations that is still happening today is the issue of terrorism. The growth of terrorism is related to the weak critical attitude of society and is exacerbated by the type of religious education which is more in the form of indoctrinative formalism and the lack of providing a place for critical reflection on students. From this background, there are two problem formulations, namely 1). How is the relationship between state and religion according to the political thoughts of Nurcholish Madjid and M. Natsir?., 2). How is the relationship between state and religion according to Nurcholish Madjid and M. Natsir in Islamic political thought in Indonesia? This research is a library research with a qualitative approach to be presented as descriptive analysis data. The results of this study are 1). that according to Nurcholish Madjid, the concept of "Islamic State" is a distortion of the balanced relationship between the state and religion. Meanwhile, according to Natsir, the concept of "Islamic State" is an unequal relationship, in which the state is a tool to achieve the goal of "perfect application of divine laws". in Indonesia. Meanwhile, M. Natsir did not agree with Pancasila as the basis of the state and agreed and even proposed the establishment of an Islamic state in Indonesia.